Synthesis and pharmacological properties of novel guanidine derivatives of quinazoline-2,4(1H,3H)-dione - Alexander A. Ozerov; Daria V. Merezhkina; Natalia A. Gurova; Lyudmila V. Naumenko; Denis A. Babkov; Victor S. Sirotenko; Roman A. Litvinov; Alena S. Taran; Nadezhda V. Stepanova; Umida M. Ibragimova; Alexander A. Spasov; Vadim A. Kosolapov (Research Results in Pharmacology)
Introduction: Na+/H+ exchanger type 1 (NHE-1) is a validated drug target for the treatment of cardiovascular and ophthalmic diseases due to the cytoprotective, anti-ischemic and anti-inflammatory properties of NHE-1 inhibitors. This article presents data on the synthesis and pharmacological activity studies of novel guanidine derivatives of quinazoline-2,4(1H,3H)-dione 6-11 and reference drugs amiloride, rimeporide, zoniporide, dexamethasone, aminoguanidine, and acetylsalicylic acid.